Developing a suite of online analysis tools for monitoring combustion efficiency in stoker boilers - Shah, Shoaib (2024)
Stoker furnaces are widely used in industry for power generation due to the flexibility of the furnace. The furnace can burn a range of solid state fuels and the stoker furnace studied in this project burns coal. Despite the flexibility observed within stoker furnaces however, combustion is more complex in stoker furnaces than gas or pulverised fuel furnaces and are difficult to operate efficiently. These difficulties result in high carbon in ash concentrations, or elevated air flow supply in the furnace, constituting a direct loss of energy. Current industry practices involve sampling the ash after combustion and employing lengthy ‘loss on ignition’ analysis to determine carbon in ash concentrations. This data is then used in efficiency assessment. This process creates a lag between the time of fuel combustion and the time at which an efficiency value is obtained. This thesis seeks to develop methods for reducing this lag through employing alternative methods for assessing combustion efficiency. Three principal methods have been studied in this thesis and are listed below. 1) The development of a rapid carbon in ash detection system (known as the microwave cavity resonator - MCR). This is achieved through the use of the cavity perturbation method, with ash samples, to generate calibration curves which can be used to estimate carbon in ash for other ash samples. 2) The implementation of thermal imaging to view and characterise the flame image and temperature data inside the stoker furnace, and to use the data as an alternative means of assessing combustion efficiency. 3) The implementation of existing industry standard combustion efficiency models and investigating the potential integration of thermal image data or rapid carbon in ash data into the models. This thesis investigates ash particle characteristics and concludes that representative sampling from the ash stream is difficult to achieve. It was found that ash samples can be dried rapidly using an 1800 W microwave, reducing the time needed for loss on ignition analysis significantly. An ash processing methodology is also discussed and it was found that particle milling is necessary before it can be used in the MCR. By supplying the MCR with rapidly dried and milled ash samples, it has been shown that instant carbon in ash values can be obtained. This reduces the lag between combustion and knowledge of carbon in ash significantly as the microwave drier and MCR system can produce a carbon in ash value within 30 minutes, compared to the LOI standard which requires more than 4 hours. Analysis on the density of the ash samples revealed a highly linear trend between ash carbon content and its tapped density. With further analysis, this feature could be used as a proxy for estimating carbon in ash. Thermal imaging within stoker furnaces is not well documented in literature. In this thesis the challenges around the implementation of a thermal imaging system are discussed. A data assessment methodology is also proposed in this research, whereby the thermal data output from the IR camera can be used towards the development of an alternative combustion efficiency assessment system. This alternative system provides a traffic light style approach to viewing combustion in the furnace whereby areas of suboptimal combustion are highlighted in red or blue, and areas which are on spec remain green. Combustion efficiency models are discussed, and the model BS845-1 is computed using the measurements completed in this thesis and also using the plant data. Data outputs from the MCR are integrated into the model. It is proposed that with further data from the thermal imaging camera, the combustion efficiency data could be integrated with the visual and thermal data through correlating the datasets. The results presented in this thesis provide a faster pathway for determining the efficiency within a stoker furnace. However further development is needed before the MCR can be used as a market ready carbon in ash detector system.